Veto Rights and Vital Interests: Formal and Informal Veto Rules for Minority Representation in Deeply Divided Societies. Issue 3 (3rd July 2022) - McCulloch, Allison; Zdeb, Aleksandra
ABSTRACT: In consociational theory, veto rights are a primary means by which ethnic groups defend their vital interests. Yet, the uses and effects of vetoes are variable. Sometimes, the veto is protective, used as a policy of last resort to facilitate inter-group cooperation and community protection. At other times, the veto is a blocking mechanism, used against minority interests or to immobilise the legislative agenda. What accounts for this variation in veto outcomes? In this article, we set out a new framework for assessing veto variability and apply the framework to three consociations – Northern Ireland, Bosnia & Herzegovina, and North Macedonia. We argue that whether a veto trajectory is blocking or protective is contingent on the interplay between three dynamics: formal institutional rules; informal forms of dispute resolution, and; the wider political environment in which these formal and informal rules intersect. Our findings aim to refine extant consociational theory, which has largely under-conceptualised these variations in veto trajectories.